INVESTIGATION OF INTERACTION OF BASIC COMPONENTS OF THE WOOD WITH UREA FORMALDEHYDE RESIN - Genov, Ivan; Ivanova, Yordanka; Valyova, Miglena (Innovation in Woodworking Industry and Engineering design, 2013)
The quantity of the wood components (cellulose, lignin, holocellulose) before and after interaction with urea formaldehyde resin (UFR), their nitrogen content and IR spectra were investigated. Increasing of the quantity of these components and of their nitrogen content was established. New bands, belonging to UFR were registered in IR spectra.